Toward spam 2.0: an evaluation of web 2.0 anti-spam methods - Hayati, Pedram; Potdar, Vidyasagar (IEEE, 2009)
Spammers have proven very powerfully adaptable, if we thwart all current spam methods, they will find new loophole to use them. Blogs, comments, forums, opinions, online communities, wikis and tags are nowadays targets for their campaigns. This paper presents analysis of current anti-spam methods in Web 2.0 for spam detection and prevention against our proposed evaluation framework. The framework is a comprehensive framework to evaluate anti-spam methods from different perspectives. Our framework shows that the need for more robust methods which are prevention based, unsupervised and do not increase user and system interaction complexity is highly demanded.